2022
DOI: 10.1155/2022/3251945
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Wood Harvesting Residues and Residual Stand Damage due to Timber Harvesting: A Case Study at PT Austral Byna in Central Kalimantan, Indonesia

Abstract: The practice of timber harvesting in natural forests which has been conducted up to now still leaves wood harvesting residue and residual stand damage. Most condition of wood harvesting residue is still good and can be utilized. The objective of this research was to determine the potency of wood harvesting residue and residual stand damage on timber harvesting in natural forests. The data on wood utilization, wood harvesting residue, and residual damage were collected from three sample plots. The sample plots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Chainsaw operators fell and process trees manually and then skidders are used to extract the timber using tree length harvesting method to the roadside to be debarked and loaded to trucks for transportation. Suhartana et al (2022) conducted a trial in a natural forest harvesting operation in Central Kalimantan Province. The main species was Meranti (Shorea spp.)…”
Section: Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Chainsaw operators fell and process trees manually and then skidders are used to extract the timber using tree length harvesting method to the roadside to be debarked and loaded to trucks for transportation. Suhartana et al (2022) conducted a trial in a natural forest harvesting operation in Central Kalimantan Province. The main species was Meranti (Shorea spp.)…”
Section: Indonesiamentioning
confidence: 99%
“…Technical faults by the harvesting crew were the main contributor to having a large share of harvesting residues (35% of total harvesting volume) including stump, buttress, butt and branches. Suhartana et al (2022) suggested recovering harvesting residues with proper timber quality for further usages in Indonesia but did not mention specific recovery techniques and machines.…”
Section: Indonesiamentioning
confidence: 99%
“…The mechanization of these activities from a technical, economic, environmental, and ergonomic point of view is essential for providing safety information for planning and decision making in planted forests [1]. Wood harvesting is the stage of the forestry process that most benefits from this advance, using self-propelled forestry machines for cutting, extracting, and processing wood, ensuring increased productivity and optimizing processes [2][3][4].…”
Section: Introductionmentioning
confidence: 99%